Investigating the implementation of mobile messaging in population screening programmes: a modified Delphi study. (November 2022) - Acharya, Amish; Judah, Gaby; Ashrafian, Hutan; Sounderajah, Viknesh; Johnstone-Waddell, Nick; Harris, Mike; Stevenson, Anne; Darzi, Ara
Abstract: Background: Mobile messaging is an increasingly important health-care communication tool. Screening programmes pose unique challenges because of the large, diverse populations invited, who might have not interacted with services previously. This study aimed to provide guidance on how screening programmes in England can effectively implement mobile messaging services. Methods: Experts based in England, from public health, policy, screening provision, communications, and academia were recruited to this Delphi study. Recommendations were derived from an evidence synthesis involving a literature review, expert scoping questionnaire, public consultation, and discussion with relevant national organisations. Experts voted upon the importance and feasibility of recommendations across two consensus rounds, using a five-point Likert scale. Items reaching consensus, defined a priori at 70%, on importance and feasibility formed core recommendations. Those reaching this threshold on importance only, were labelled desirable. All items were discussed at an expert meeting to determine suitability. Ethical approval was obtained (20IC6088), and participants provided informed consent. Findings: 33 experts representing all 11 screening programmes were enrolled, with 100% retention across rounds. Of the initial 101 items, 23 (23%) reached consensus. These core recommendations were divided across six domains: message content, timing, delivery, evaluation, security, and research. They included the use of general practitioner endorsement and limiting message length to 320 characters. A further 17 items were considered desirable; for example, introducing greater functionality such as bidirectional and tailored messaging. Interpretation: Findings will facilitate the effective use of mobile messaging across screening and will form national guidance for services. This guidance will enable programmes to overcome implementation challenges and facilitate uptake of screening invitations. As representation of experts was skewed toward cancer versus non-cancer screening programmes, the generalisability of these findings must be carefully considered. However, the list of desirable items provides areas for future consideration for all programmes, as technological innovation in messaging grows. Funding: National Institute for Health and Care Research Imperial Patient Safety Translational Research Centre.